Transport Network Analysis: a Case Study of Perambalur District (Tamil Nadu) Using GIS (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Road transport is the main mode of transportation in developing countries, as it allocates flexibility to the commonly scattered spatial configuration. Improving the road transport system increases accessibility and mobility, thus reducing travel costs and travel time. A good road transport system can bring many benefits to a country because transport is a mechanism for economic and social progress. Hence, the Road Transport System across the Perambalur District was selected as the study area for the preparation of the basic map. In this study area, we use the Alpha, Beta, Gamma, Cyclometric, Pie Index, Eta Index, Theta Index, Grid Tree Proportion Index, Network Density, Connectivity, Accessibility and Detour Index parameters to understand the topology pattern and road transport system in the study area. In this study, ArcGIS 9.3 software is used to digitize traffic network data, build a network dataset, and analyse the network using graphical theoretical steps to model network configuration. From Perambalur towns to other vertices, the distance is small and so it can be connected to all the vertices easily which indicates that the transport network pattern is good in Perambalur town.
Keywords: India; transport; connectivity; Perambalur District; GIS